P178 How does comorbidity influence the likelihood of significant findings when investigating iron deficiency anaemia?. (19th June 2022) - Masterman, Benjamin; Saunsbury, Emma; Perry, Rachel
Abstract : Introduction: Iron deficiency anaemia (IDA) has many potential non-gastroenterological causes, including functional IDA, primarily caused by chronic disease. The current study asks whether increasing comorbidity reduces the likelihood of significant findings at endoscopy when investigating IDA. Methods: Inpatient and outpatient referrals to a single gastroenterology department were retrospectively reviewed. Electronic health records were used to obtain past medical history, date of death/follow-up time, biochemistry, radiology and endoscopy results. Comorbidity was measured using the modified Charlson Comorbidity Index (mCCI), a validated marker of morbidity and mortality in gastroenterological (GI) illnesses. Statistical analyses were primarily chi 2, t-test and logistic regression, all using Stata V16 (StataCorp). Results: 374 referrals were analysed with average age 72.4 years (range 17, 96) and average haemoglobin (Hb) 91.3g/L (40, 155). Inpatient referrals (n=178) had a higher mCCI than outpatients (n=196) with OR 1.58 (95%CI 1.41, 1.78; p<0.001). Increasing mCCI was also associated with increasing age, normo/macrocytosis, normal/raised ferritin and use of antiplatelet, anticoagulant or both. Higher mCCI level also made invasive investigation modalities less likely, with OR for OGD and colonoscopy 0.27 (95%CI 0.13, 0.55 p<0.001) for each unit increase in mCCI. Increasing mCCI gave a mortality rate ratio of 1.32 (95%CI 1.21, 1.44; p<0.001). There was no association between mCCI and GI bleeding after adjusting for age, sex and inpatient status ( Table 1 ; OR 1.06; 95%CI 0.94, 1.19; p=0.362). GI malignancy was less likely with increasing mCCI both before and after adjustment for confounders ( Table 1 ; OR 0.70; 95%CI 0.54, 0.90; p=0.006). Conclusions: Comorbidity is highlighted as an important factor when investigating IDA, independent of age and setting, as it indicates a lower life expectancy and lower likelihood of GI malignancy as the underlying cause of IDA. This may encourage clinicians to avoid endoscopy in selected cases where risks of endoscopy are high and comorbidity itself provides a plausible explanation for IDA.